Daub and preparation method thereof
Through the formulation of mortar with specific components and proportions, the problems of chemical corrosion resistance, permeability resistance and insufficient mechanical strength of existing mortar in extreme environments are solved, and the long-term use of high-performance polymer structural mortar in harsh environments is achieved.
Patent Information
- Application Number
- CN202510709926.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-09-09
AI Technical Summary
Existing mortars have insufficient chemical corrosion resistance, poor permeability resistance, and insufficient mechanical strength under extreme environments, which shortens the life of industrial wastewater treatment facilities.
A mortar formula containing epoxy resin, micro-nano alumina modified fluorosilicone polymer, silica powder, diabase powder, fumed silica and other components is adopted, and a specific proportion of component A and component B are mixed to form a high-performance polymer structural mortar. The uniform dispersion of micro-nano alumina in the fluorosilicone polymer and the chemical inertness of the CF bond are utilized to improve the density and heat resistance of the coating.
The compressive strength, chemical corrosion resistance and permeability resistance of the mortar are significantly improved, and the heat deformation temperature is increased to 200℃-250℃, maintaining high performance in high temperature, high humidity, strong acid and strong alkali environments.
Smart Images

Figure BDA0005426806490000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrial wastewater treatment, and in particular to a clay and a preparation method thereof. Background Art
[0002] Industrial wastewater treatment facilities often face problems such as corrosion, penetration and structural damage. Traditional anti-corrosion coatings and putties are prone to cracking and peeling during long-term use, which shortens the life of industrial wastewater treatment facilities.
[0003] Although existing mortar has certain anti-corrosion and reinforcement effects, it still has the following problems in extreme environments: (1) Insufficient chemical corrosion resistance: Industrial wastewater often contains a variety of corrosive substances, such as acids, alkalis, salts, etc. Some existing mortars may degrade, crack or fall off when exposed to these corrosive environments for a long time, resulting in a decrease in their protective effect; (2) Poor permeability: During long-term use, moisture and corrosive media can easily penetrate into the existing mortar, causing the mortar to fail, thereby affecting the structural integrity and service life of the facility; (3) Insufficient mechanical strength: Existing mortars are insufficient in mechanical strength, especially in terms of compressive strength, tensile strength and impact strength. They cannot meet the use requirements in extreme environments and are prone to cracking, peeling and other problems. Summary of the Invention
[0004] The purpose of the invention is to overcome the defects of the existing mortar, such as insufficient chemical corrosion resistance, poor permeability and insufficient mechanical strength under harsh environments.
[0005] In order to achieve the above object, the present invention provides a clay, which comprises at least:
[0006] Component A:
[0007] Epoxy resin: 40 to 50 parts;
[0008] Micro-nano alumina modified fluorosilicone polymer: 10 to 20 parts;
[0009] Silicon powder: 10 to 15 parts;
[0010] Diabase powder: 15 to 20 parts;
[0011] Fumed silica: 6 to 8 parts;
[0012] Epoxy diluent: 5 to 10 parts;
[0013] Component B:
[0014] Curing agent: 50 to 60 parts;
[0015] Curing accelerator: 1 to 3 parts;
[0016] Talc: 20-30 parts;
[0017] Silicon powder: 10 to 15 parts.
[0018] Preferably, the mass ratio of the component A to the component B is 1:(1-1.2).
[0019] Preferably, in component A, the epoxy resin comprises any one of bisphenol A epoxy resin and bisphenol F epoxy resin.
[0020] Preferably, the particle size of the micro-nano alumina modified fluorosilicone polymer is 50 nm to 100 nm.
[0021] Preferably, in component A, the epoxy diluent comprises any one of butyl glycidyl ether and ethylene glycol diglycidyl ether.
[0022] Preferably, in component B, the curing agent is a polyamine curing agent.
[0023] Preferably, the polyamine curing agent is selected from any one of polyetheramine T-403 and Ancamine 2606.
[0024] Preferably, the particle size of the silicon micropowder is 1000 mesh to 1250 mesh.
[0025] Preferably, the curing accelerator is N,N-dimethylbenzylamine.
[0026] The present invention also provides a method for preparing the above-mentioned cement, comprising the following steps:
[0027] S1, Preparation of Component A:
[0028] Add epoxy resin, micro-nano alumina modified fluorosilicone polymer, and epoxy diluent into a blender and stir evenly; add silica powder, diabase powder, and fumed silica into the blender and stir evenly to obtain component A;
[0029] S2, Preparation of Component B:
[0030] Add curing agent, curing accelerator, talc and silica powder into a blender and mix well to obtain component B;
[0031] The component A and the component B are mixed in a mass ratio of 1: (1 to 1.2), and stirred evenly to obtain the cement.
[0032] Compared with the prior art, the beneficial effects of the present invention include at least:
[0033] A mortar of the present invention comprises at least component A and component B, wherein component A comprises epoxy resin, micro-nano alumina-modified fluorosilicone polymer, microsilica diabase powder, fumed silica, and epoxy diluent, and component B comprises a curing agent, a curing accelerator, talcum powder, and microsilica powder. After the micro-nano alumina is uniformly dispersed in the fluorosilicone polymer matrix, its rigidity advantage enables it to greatly limit the relative movement of polymer molecular chains, thereby improving the compressive strength of the mortar; the CF bond in the fluorosilicone polymer molecule has extremely strong chemical inertness, and it produces a synergistic effect with the micro-nano alumina with good chemical stability, so that the mortar can resist the erosion of various chemical substances; after the micro-nano alumina is filled into the molecular gaps of the fluorosilicone polymer, the coating of the mortar is denser, thereby greatly reducing the permeability of the medium; the high thermal conductivity of the micro-nano alumina is combined with the good heat resistance of the fluorosilicone polymer, which greatly improves the thermal deformation temperature of the mortar, so that the coating prepared from the mortar has strong hydrophobicity, low water absorption, and high barrier performance, and is more suitable for use in the field of industrial wastewater treatment. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further illustrated below with reference to embodiments and comparative examples.
[0035] Example 1
[0036] The present embodiment provides a clay comprising, by weight:
[0037] Component A:
[0038] Bisphenol A epoxy resin: 45 parts;
[0039] Micro-nano alumina modified fluorosilicone polymer: 15 parts;
[0040] Silicon powder: 12 parts;
[0041] Diabase powder: 18 parts;
[0042] Fumed silica: 7 parts;
[0043] Butyl glycidyl ether: 8 parts;
[0044] Component B:
[0045] Polyetheramine T-403: 55 parts;
[0046] N,N-dimethylbenzylamine: 2 parts;
[0047] Talc: 25 parts;
[0048] Silicon powder: 12 parts.
[0049] Add bisphenol A epoxy resin, micro-nano alumina modified fluorosilicone polymer, and butyl glycidyl ether into a blender and stir evenly; add silica powder, diabase powder, and fumed silica into the blender and stir evenly to obtain component A;
[0050] S2, Preparation of Component B:
[0051] Add polyetheramine T-403, N,N-dimethylbenzylamine, talc and silica powder into a blender and mix well to obtain component B;
[0052] Mix component A and component B in a mass ratio of 1:1 and stir evenly to obtain a high-performance polymer structural mortar.
[0053] The epoxy value of the bisphenol A epoxy resin is 0.44 mol / 100 g to 0.55 mol / 100 g, the particle size of the silica powder is 1000 mesh to 1250 mesh, the particle size of the diabase powder is 500 mesh to 600 mesh, and the particle size of the talc powder is 1250 mesh.
[0054] Example 2
[0055] The present embodiment provides a clay comprising, by weight:
[0056] Component A:
[0057] Bisphenol A epoxy resin: 50 parts;
[0058] Micro-nano alumina modified fluorosilicone polymer: 20 parts;
[0059] Silica powder: 15 parts;
[0060] Diabase powder: 20 parts;
[0061] Fumed silica: 8 parts;
[0062] Ethylene glycol diglycidyl ether: 10 parts;
[0063] Component B:
[0064] Polyetheramine T-403: 60 parts;
[0065] N,N-dimethylbenzylamine: 3 parts;
[0066] Talc: 30 parts;
[0067] Silicon powder: 15 parts.
[0068] Add bisphenol A epoxy resin, micro-nano alumina modified fluorosilicone polymer, and ethylene glycol diglycidyl ether into a blender and stir evenly; add silica powder, diabase powder, and fumed silica into the blender and stir evenly to obtain component A;
[0069] S2, Preparation of Component B:
[0070] Add polyetheramine T-403, N,N-dimethylbenzylamine, talc and silica powder into a blender and mix well to obtain component B;
[0071] Component A and component B are mixed in a mass ratio of 1:1.2 and stirred evenly to obtain a high-performance polymer structural mortar.
[0072] Example 3
[0073] The present embodiment provides a clay comprising, by weight:
[0074] Component A:
[0075] Bisphenol A epoxy resin: 40 parts;
[0076] Micro-nano alumina modified fluorosilicone polymer: 10 parts;
[0077] Silicon powder: 10 parts;
[0078] Diabase powder: 15 parts;
[0079] Fumed silica: 6 parts;
[0080] Butyl glycidyl ether: 5 parts;
[0081] Component B:
[0082] Ancamine 2606: 50 parts;
[0083] N,N-dimethylbenzylamine: 1 part;
[0084] Talc: 20 parts;
[0085] Silicon powder: 10 parts.
[0086] Add bisphenol A epoxy resin, micro-nano alumina modified fluorosilicone polymer, and butyl glycidyl ether into a blender and stir evenly; add silica powder, diabase powder, and fumed silica into the blender and stir evenly to obtain component A;
[0087] S2, Preparation of Component B:
[0088] Add Ancamine 2606, N,N-dimethylbenzylamine, talc and silica powder into a blender and mix well to obtain component B;
[0089] Mix component A and component B in a mass ratio of 1:1 and stir evenly to obtain a high-performance polymer structural mortar.
[0090] Example 4
[0091] The present embodiment provides a clay comprising, by weight:
[0092] Component A:
[0093] Bisphenol A epoxy resin: 48 parts;
[0094] Micro-nano alumina modified fluorosilicone polymer: 18 parts;
[0095] Silica powder: 14 parts;
[0096] Diabase powder: 19 parts;
[0097] Fumed silica: 7.5 parts;
[0098] Ethylene glycol diglycidyl ether: 9 parts;
[0099] Component B:
[0100] Ancamine 2606: 58 parts;
[0101] N,N-dimethylbenzylamine: 2.5 parts;
[0102] Talc: 28 parts;
[0103] Silica powder: 14 parts.
[0104] Add bisphenol A epoxy resin, micro-nano alumina modified fluorosilicone polymer, and ethylene glycol diglycidyl ether into a blender and stir evenly; add silica powder, diabase powder, and fumed silica into the blender and stir evenly to obtain component A;
[0105] S2, Preparation of Component B:
[0106] Add Ancamine 2606, N,N-dimethylbenzylamine, talc and silica powder into a blender and mix well to obtain component B;
[0107] Component A and component B are mixed in a mass ratio of 1:1.1 and stirred evenly to obtain a high-performance polymer structural mortar.
[0108] Comparative Example 1
[0109] This comparative example provides a kind of clay, according to weight parts, comprising:
[0110] Component A:
[0111] Bisphenol A epoxy resin: 45 parts;
[0112] Silicon powder: 12 parts;
[0113] Diabase powder: 18 parts;
[0114] Fumed silica: 7 parts;
[0115] Butyl glycidyl ether: 8 parts;
[0116] Component B:
[0117] Polyetheramine T-403: 55 parts;
[0118] N,N-dimethylbenzylamine: 2 parts;
[0119] Talc: 25 parts;
[0120] Silicon powder: 12 parts.
[0121] Add bisphenol A epoxy resin and butyl glycidyl ether into a blender and stir evenly; add silica powder, diabase powder and fumed silica into the blender and stir evenly to obtain component A;
[0122] S2, Preparation of Component B:
[0123] Add polyetheramine T-403, N,N-dimethylbenzylamine, talc and silica powder into a blender and mix well to obtain component B;
[0124] Mix component A and component B in a mass ratio of 1:1 and stir evenly to obtain a high-performance polymer structural mortar.
[0125] Comparative Example 2
[0126] This comparative example provides a kind of clay, according to weight parts, comprising:
[0127] Component A:
[0128] Bisphenol A epoxy resin: 45 parts;
[0129] Fluorosilicone polymer grafted POSS: 15 parts;
[0130] Silicon powder: 12 parts;
[0131] Diabase powder: 18 parts;
[0132] Fumed silica: 7 parts;
[0133] Butyl glycidyl ether: 8 parts;
[0134] Component B:
[0135] Polyetheramine T-403: 55 parts;
[0136] N,N-dimethylbenzylamine: 2 parts;
[0137] Talc: 25 parts;
[0138] Silicon powder: 12 parts.
[0139] Add bisphenol A epoxy resin, fluorosilicone polymer grafted POSS, and butyl glycidyl ether into a blender and stir evenly; add silica powder, diabase powder, and fumed silica into the blender and stir evenly to obtain component A;
[0140] S2, Preparation of Component B:
[0141] Add polyetheramine T-403, N,N-dimethylbenzylamine, talc and silica powder into a blender and mix well to obtain component B;
[0142] Mix component A and component B in a mass ratio of 1:1 and stir evenly to obtain a high-performance polymer structural mortar.
[0143] Comparative Example 3
[0144] This comparative example provides a kind of clay, according to weight parts, comprising:
[0145] Component A:
[0146] Bisphenol A epoxy resin: 45 parts;
[0147] Micro-nano alumina modified fluorosilicone polymer: 15 parts;
[0148] Silicon powder: 12 parts;
[0149] Diabase powder: 18 parts;
[0150] Fumed silica: 7 parts;
[0151] Butyl glycidyl ether: 8 parts;
[0152] Component B:
[0153] Triethylenetetramine: 55 parts;
[0154] N,N-dimethylbenzylamine: 2 parts;
[0155] Talc: 25 parts;
[0156] Silicon powder: 12 parts.
[0157] Add bisphenol A epoxy resin, micro-nano alumina modified fluorosilicone polymer, and butyl glycidyl ether into a blender and stir evenly; add silica powder, diabase powder, and fumed silica into the blender and stir evenly to obtain component A;
[0158] S2, Preparation of Component B:
[0159] Add triethylenetetramine, N,N-dimethylbenzylamine, talc and silica powder into a blender and mix well to obtain component B;
[0160] Component A and component B are mixed in a mass ratio of 1:3 and stirred evenly to obtain a high-performance polymer structural mortar.
[0161] The high-performance polymer structural mortar prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was tested for tensile strength, elongation at break, compressive strength, bonding strength, glass transition temperature, and chemical corrosion resistance to obtain the test results shown in Table 1.
[0162] Table 1 Main mechanical properties test results of high performance polymer structural mortar
[0163]
[0164] As can be seen from Table 1, the tensile strength, elongation at break, compressive strength, bonding strength, glass transition temperature, and chemical corrosion resistance of the high-performance polymer structural mortar prepared in Examples 1 to 4 are significantly better than those in Comparative Examples 1 to 3, indicating that the addition of micro-nano alumina-modified fluorosilicone polymer can significantly improve the physical strength, high temperature resistance, and corrosion resistance of the coating. Micro-nano alumina (particle size precisely controlled at 50-100nm) acts as a rigid filler. With its nanometer-level microscopic size, after being uniformly dispersed in the fluorosilicone polymer matrix, it acts like countless tiny "nails," producing a significant "pinning effect." This effect greatly limits the relative movement of the polymer molecular chains, resulting in a qualitative leap in the compressive strength of the mortar.
[0165] Fluorosilicone polymers possess a unique chemical structure, and the C-H bonds within their molecules exhibit strong chemical inertness, making them resistant to corrosion from a wide range of chemicals. Micro-nano alumina, with its excellent chemical stability, creates a synergistic effect with fluorosilicone polymers. In rigorous chemical environment testing, the modified mortar retained ≥95% strength after being immersed in a 10% H2SO4 or NaOH solution for 30 days. In contrast, ordinary mortar exhibits a significant decrease in strength under the same conditions, and may even experience coating peeling and damage.
[0166] The addition of micro-nano alumina also causes significant changes in the coating structure. It fills the molecular gaps of the fluorosilicone polymer, making the coating structure denser. This densified structure acts like a solid barrier, greatly reducing the permeability of the medium. In terms of high-temperature resistance, the high thermal conductivity (30W / m·K) of micro-nano alumina combined with the good heat resistance of fluorosilicone polymers produces a powerful synergistic effect. The heat deformation temperature of ordinary mortar is only 80°C, and it is prone to softening and deformation in high-temperature environments, affecting its performance. After adding micro-nano alumina fluorosilicone polymers, the heat deformation temperature of the mortar is greatly increased to 200°C-250°C.
[0167] The curing agent polyetheramine T-403 has the characteristics of high flexibility, impact resistance and low viscosity. Ancamine2606 has the advantages of resistance to moisture and heat, chemical corrosion and fast curing speed. As an alternative to traditional curing agents, it effectively improves the performance of polymer structural mortar.
[0168] In summary, a high-performance polymer structural mortar of the present invention comprises at least component A and component B, wherein component A comprises epoxy resin, micro-nano alumina-modified fluorosilicone polymer, silicon micropowder diabase powder, fumed silica, and epoxy diluent; component B comprises a curing agent, a curing accelerator, talcum powder, and silicon micropowder; the micro-nano alumina and the fluorosilicone polymer produce a synergistic effect, so that the prepared mortar has excellent corrosion resistance, permeability resistance and mechanical strength, and can be used for a long time in harsh environments such as high temperature, high humidity, strong acid, and strong alkali.
[0169] Although the present invention has been described in detail through the above preferred embodiments, it should be understood that the above description is not intended to limit the present invention. After reading the above description, various modifications and substitutions of the present invention will become apparent to those skilled in the art. Therefore, the scope of protection of the present invention should be defined by the appended claims.
Claims
1. A clay, characterized in that According to parts by weight, the clay comprises at least: Component A: Epoxy resin: 40 to 50 parts; Micro-nano alumina modified fluorosilicone polymer: 10 to 20 parts; Silicon powder: 10 to 15 parts; Diabase powder: 15 to 20 parts; Fumed silica: 6 to 8 parts; Epoxy diluent: 5 to 10 parts; Component B: Curing agent: 50 to 60 parts; Curing accelerator: 1 to 3 parts; Talc: 20-30 parts; Silicon powder: 10 to 15 parts.
2. The clay according to claim 1, wherein By mass ratio, the component A:component B=1:(1-1.2).
3. The clay according to claim 1, wherein In component A, the epoxy resin comprises any one of bisphenol A epoxy resin and bisphenol F epoxy resin.
4. The clay according to claim 1, wherein The particle size of the micro-nano alumina modified fluorosilicone polymer is 50nm-100nm.
5. The clay according to claim 1, wherein In component A, the epoxy diluent comprises either butyl glycidyl ether or ethylene glycol diglycidyl ether.
6. The clay according to claim 1, wherein In component B, the curing agent is a polyamine curing agent.
7. The mastic as claimed in claim 6, characterized in that The polyamine curing agent is selected from any one of polyetheramine T-403 and Ancamine 2606.
8. The clay according to claim 1, wherein The particle size of the silicon micropowder is 1000 mesh to 1250 mesh.
9. The clay according to claim 1, wherein The curing accelerator is N,N-dimethylbenzylamine.
10. A method for preparing the cement according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, Preparation of Component A: Add epoxy resin, micro-nano alumina modified fluorosilicone polymer, and epoxy diluent into a blender and stir evenly; add silica powder, diabase powder, and fumed silica into the blender and stir evenly to obtain component A; S2, Preparation of Component B: Add curing agent, curing accelerator, talc and silica powder into a blender and mix well to obtain component B; The component A and the component B are mixed in a mass ratio of 1: (1 to 1.2), and stirred evenly to obtain the cement.